2019
DOI: 10.3390/ijerph16214212
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Social Context on Motivation towards the Practice of Physical Activity and the Intention to be Physically Active

Abstract: According to WHO data, only around 20% of adolescents participate in physical activity (PA) during their free time. The social context can act as a support for adolescents to do PA, given the effect that both parents, friends and teachers have on young people’s behaviour owing to the large amount of time and influence they have on them. Therefore, the aim of this study is to analyse the role of the social context on adolescents’ motivation to practise PA and their intention to be physically active. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
2
14
0
3
Order By: Relevance
“…Interactions with a supportive social environment and mastery experiences were perceived as facilitating physical activity [ 19 ]. These findings align with theories that describe how behaviour is influenced by social interactions and interpersonal environments [ 21 ]. Interactions that support the individual’s autonomy (e.g., mastery experiences) will increase the desired behaviour while those that are controlling (e.g., authoritarian style) will decrease motivation and enjoyment.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interactions with a supportive social environment and mastery experiences were perceived as facilitating physical activity [ 19 ]. These findings align with theories that describe how behaviour is influenced by social interactions and interpersonal environments [ 21 ]. Interactions that support the individual’s autonomy (e.g., mastery experiences) will increase the desired behaviour while those that are controlling (e.g., authoritarian style) will decrease motivation and enjoyment.…”
Section: Introductionsupporting
confidence: 89%
“…Young adults with CCHD have reported feelings of uncertainty, being different, and a lack of knowledge about the impact of their diagnosis, which was in part attributed to their exclusion from discussions between their parents and healthcare providers. Although it is recognized that the activity environments differ between children (e.g., school-based activities, lessons) and adults [ 37 ], the importance of motivation and competence have also been recognized in relation to the physical activity of adolescents with CCHD [ 19 , 21 ]. Children in this study were 6 to 12 years of age and thus differed in relation to their autonomy for physical activity participation and their capacity to interpret their experiences and interactions with their social environment.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, el cambio de comportamiento no es un proceso fácil; y el aumento de la actividad física es particularmente desafiante debido a que existen varias barreras que impiden la práctica de actividad física, así como diversas influencias que promueven el comportamiento sedentario (Chambliss, 2015): la tecnología por ejemplo ha revolucionado la forma en que opera nuestro mundo, y en consecuencia los estilos de vida de las personas (Toto y Strazzeri, 2018); por otro lado, el contexto social puede actuar como apoyo para que los adolescentes realicen actividad física, dado el efecto que tanto padres como amigos y profesores tienen en el comportamiento de los jóvenes debido al tiempo que pasan con ellos y la influencia que puedan ejercer (Trigueros, Aguilar-Parra, Cangas, Fernández-Batanero y Álvarez, 2019). Y es aquí donde la teoría de la autodeterminación juega un papel importante, la cual se describe como una macroteoria de la motivación humana, la emoción y la personalidad, que proporciona una comprensión del por qué las personas inician y persisten en los comportamientos (Deci & Ryan, 2011); dicha teoría se ha aplicado con éxito en una amplia variedad de contextos, incluida la ecología, la psicoterapia, el trabajo, la educación, el ejercicio y los deportes (Haerens et al, 2010).…”
Section: Introductionunclassified
“…The previous research that adopted the trans-contextual model have thus exclusively focused on the role of perceived positive behavior from PE teachers on students’ learning outcomes, both in a PE and leisure-time physical activity context. There are only a few studies that have demonstrated the unfavorable role of perceived negative behavior from PE teachers on students’ leisure-time physical activity [ 25 , 32 , 33 , 34 ]. To the best of our knowledge, however, no studies to date have applied the entire motivational sequence proposed in the trans-contextual model in investigating the relationship between perceived negative (i.e., controlling) behavior exhibited by teachers in an educational context (i.e., PE context) and students’ actual participation in physical activity outside of school.…”
Section: Introductionmentioning
confidence: 99%